Vozrast, rosto-vesovye pokazateli i masterstvo gimnastov-yuniorov - Arkayev, L. Ya.; Rosin, E. Yu. (Teorija i Praktika fiziceskoj Kul'tury, 1999)
The authors of this paper analyze and discuss the interrelations of age and mastery in gymnastics using the large factological material of the World Youth Games of 1998 in Moscow. They appeal to the international gymnastics federations (FIG, UEC and others) to take into consideration the necessity of the age and the main parameters of physical status in gymnasts-juniors when elaborating the conditions of competitions' organization and the demands to the mastery of the prominent international juniors competitions.